VITALISASI PENDIDIKAN ISLAM MODERAT (Ikhtiar Membongkar Radikalisme di Perguruan Tinggi) - Firdausih (Journal Multicultural of Islamic Education, 2023)
The pattern of the Radicalism movement covers college intellectual groups, both lecturers and students who have a superficial understanding of charity. The Radicals believe that the colleges are a fertile soil in rejuvenating the seeds of radicalism more than the general colleges. Colleges were chosen as ideological cadres that could one day spread the virus of radicalism massively and explosively across colleges and layers of society. The radical movement and radicalism in the colleges responded critically by the government and some college leaders by issuing information about the threat of the movement Anti Pancasila and NKRI. Such a move as a way to contain and destroy the movement of radicalization in the college which also needs to be followed by the vitalization and internalization of moderate Islamic education, both through the policy of the college leadership, the formulation of curricula, lectures and activities of lecturers and scholarship.From the revitalization of moderate Islamic education is expected that radical movements and the spread of college radicalism can easily be destroyed.